PENINGKATAN MEMBACA PEMAHAMAN CERITA FANTASI SISWA SMP MELALUI PENGGUNAAN MEDIA FILM ANIME SUBTITLE BAHASA INDONESIA (Improvement of Reading Comprehension of Fantasy Stories for Junior High School Students Using Anime Films Media with Indonesian Subtitles) - Rina Andriani (SAWERIGADING, 2022)
This study aims to determine the difference in the improvement of reading comprehension of fantasy stories on junior high school students between the experimental class using animated subtitle  Indonesian language film media and the control class using conventional learning. The research method used is an experimental method, with a non-equivalent control group design. The subjects of this study were class VII–H as the experimental class and class VII–D as the control class at one of the junior high schools located in Bandung for the 2020-2021 academic year. The results showed that there was a significant difference between the average value of the experimental class which was higher than the control class and the normalized gain test t count of 2.13 and t table of 1.69 with df = 32, because t count t table then H0 is rejected or H1 is used so that it can It is concluded that the use of Indonesian language anime film media is effective in increasing the ability to read and understand fantasy stories for junior high school students compared to conventional learning.